The Protocol-Personalized Perioperative Hemodynamic Management as Part of the ERAS Protocol in Abdominal Surgeries - K. Е. Kharlamov; M. Ya. Yadgarov; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии, 2021)
One of the options for solving the problem of a “non-standard” patient undergoing a major and traumatic operation, perhaps, is the protocol-personalized approach to hemodynamic management.The objective: to study the efficacy and safety of using a modified protocol-personalized approach to hemodynamic management during surgical interventions on abdominal organs in elderly and senile patients.Subjects and Methods. A randomized prospective-retrospective clinical trial was conducted in parallel groups: Group 1 (control) - standard management of the perioperative period; Group 2 - standard management supplemented by the protocol-personalized approach to hemodynamic management.Results. Patients in the main group had the best parameters as per MACE outcomes (RR: 0.462, [95% CI: 0.251-0.850] p = 0.038). In the intra- and postoperative period, patients in the control group had a relatively higher risk of arrhythmias (RR: 2.517 [95% CI: 1.218; 5,200] p = 0.017).Conclusion. The use of the protocol-personalized approach results in better MACE outcomes (RR: 0.462, 95% CI: 0.251-0.850; p = 0.038) during surgical interventions on the abdominal organs in elderly and senile patients, and also, reduces the risk of arrhythmias (RR: 2.517, 95% CI:1.218; 5.200) p = 0.017.